Cryoscopic Osmometer for Studying Cryobiological Fluids - Kuchkov, V. N.; Zinchenko, V. D. (Problems of Cryobiology and Cryomedicine, 2011)
The factors affecting the accuracy of temperature measurements in biological fluids in cryoscopic osmometer: heat capacity of temperature gauge, sample mass, integral heat conductivity of the medium and temperature difference between the sample and coolant, were analyzed. The results of analysis were used when designing cryoscopic cell to investigate the liquids with an increased inclination to overcooling. Cryoscopic osmometer with this cell enables the measuring of freezing temperature of such systems with Â±0.005Â°Caccuracy.